2017
DOI: 10.1101/130179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-scale mutational signatures of aflatoxin in cells, mice and human tumors

Abstract: Aflatoxin B1 (AFB1) is a mutagen and IARC Group 1 carcinogen that causes hepatocellular carcinoma (HCC). Here we present the first whole genome data on the mutational signatures of AFB1 exposure from a total of > 40,000 mutations in four experimental systems: two different human cell lines, and in liver tumors in wild-type mice and in mice that carried a hepatitis B surface antigen transgene -this to model the multiplicative effects of aflatoxin exposure and hepatitis B in causing HCC. AFB1 mutational signatur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 59 publications
6
24
0
1
Order By: Relevance
“…2D, p= 9.50×10 -41 , 6.33×10 -91 and 5.69×10 -33 respectively, Chi-squared tests). Furthermore, TC-NER proficiency decreases with increasing distance to the transcription start site (Conaway and Conaway 1999;Huang et al 2017;Boot et al 2018). Consistent with this, T>A, T>C and T>G mutations all showed decreased transcriptional strand bias towards the 3' end of transcripts ( Fig.…”
Section: T>n Mutations Att>act Mutationssupporting
confidence: 77%
“…2D, p= 9.50×10 -41 , 6.33×10 -91 and 5.69×10 -33 respectively, Chi-squared tests). Furthermore, TC-NER proficiency decreases with increasing distance to the transcription start site (Conaway and Conaway 1999;Huang et al 2017;Boot et al 2018). Consistent with this, T>A, T>C and T>G mutations all showed decreased transcriptional strand bias towards the 3' end of transcripts ( Fig.…”
Section: T>n Mutations Att>act Mutationssupporting
confidence: 77%
“…This finding 422 suggests that the mutational processes that underlie these signatures are only active after 423 oncogenic transformation, or that mutagen exposure in liver cancer (progenitor) cells is 424 different from in vivo mouse ASCs and in vitro human ASCs. Liver cancer-specific Signature 425 24, for example, is associated with Aflatoxin intake(Huang et al 2017), a substance to 426 which our mice and organoids were not exposed. In addition, Signature 1 and Signature 5,427 which have been previously associated with age (Blokzijl et al 2016; Alexandrov et al 428 2015), did not have an increased contribution in the ASCs of progeroid Ercc1 -/Δ mice.…”
mentioning
confidence: 99%
“…Indeed, non-human cell lines are known to differ in DNA damage susceptibility (MacRae et al 2015), e.g. exposing aflatoxin to cell lines, mouse tumors and human tumors results in great diversity in mutation profiles (Huang et al 2017). Likewise, cisplatin signatures characterized with cell lines of different model organisms (Szikriszt et al 2016;Meier et al 2014) do not recapitulate the cisplatin patterns recently found in human cancer L.…”
Section: Discussionmentioning
confidence: 99%